Optimizing the Use of Palm Fiber to Increase Stability and Deformation Resistance in Asphalt Concrete Mixes - Alifuddin, Andi; Massara, Asma; Muhammad, Vadhel; Mardin, Nurul Ihsani (Politeknik Negeri Ujung Pandang, 2024)
Modifying asphalt binder materials with fiber reinforcement is one approach to improving the performance of asphalt concrete mixtures. This research aims to evaluate the effect of optimal palm fiber concentration on strengthening and improving the properties of the mixture and rutting resistance. Test specimens were made with four variations in the composition of a mixture of different palm fiber percentages (0%, 0.4%, 0.6%, and 0.85) with lengths (0.4 cm, 0.6 cm, 0.8 cm, and 1.0 cm) using an optimum asphalt content of 6% to evaluate the properties of the asphalt concrete mixture based on the Marshall Test. In comparison, the rutting indicator was evaluated using a wheel tracking tool with four variations in the percentage of palm fiber to an optimal length of 0.8 cm. The results of the Marshall test research showed that palm fiber increased stability by 6%, with the highest stability at a percentage of palm fiber of 0.6% with a length of 0.8 cm 1210.45 kg, higher than the normal mixture with a stability value of 1142.59 kg, VIM value decreased by 14% compared to the normal mixture and increased the flexibility of the mixture at the optimum percentage composition of palm fiber 0.6% length 8 cm by 4%. Fibre wheel tracking test results show that adding fiber fibers increases the groove and rutting resistance of optimum fiber by 53% with a total deformation value of 0.856 mm, dynamic stability of 5727 passes/mm, and a deformation rate of 0.007/mm/minute. Palm fiber is not strong enough to withstand heat due to a mixing temperature of 150oC and a compaction temperature of 140oC, with a higher risk of fiber damage